Sistem Informasi Geografis Industri Kecil Dan Menengah (IKM) Pada Kota Jayapura - Widiyantoro, M. Riandi; Robo, Salahudin; Ramadhani, Alissa Putri (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The development of Small and Medium Industries (IKM) in a region is one of the efforts to encourage regional economic growth. The development of IKM in Jayapura City itself has increased from year to year. However, the current condition, the existence and location of IKM is still difficult to reach by the general public due to the lack of information about the (IKM) itself. The purpose of this research is to build a geographic information system as a means of society to get information about IKM in Jayapura City. The process of analyzing geographic information system data in this study was clustered data into three parts, namely input data, data classification and output data. This study uses the analysis method of Performance, Information, Economy, Control, Efficiency and Service (PIECES) to identify problems, design the Unified Modeling Language (UML) method, use the Waterfall development method and the Black Box testing method. This research produces a Small and Medium Industry (IKM) Geographical Information System in Jayapura City which is equipped with maps, travel routes and descriptions of the IKM chosen by the user or community. With this system, it can help and minimize people's time in finding information on the location of IKM